METODE TARTILUNA DAN SMART TV: STRATEGI PENGENALAN HURUF HIJAIYYAH UNTUK ANAK USIA DINI DI TK NASIMA SEMARANG - Bahtiar, Sofian Ahadi; Lia, Naila Fikrina Afrih (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The Hijaiyyah alphabet is an essential component in understanding the two primary guides in life: the Quran and the Hadith. Therefore, it is important to introduce it to children at an early age, through both formal and non-formal education. Teaching the Hijaiyyah alphabet to young children often presents challenges such as the lack of engaging methods, low student interest, and the inappropriate use of digital technology in learning. This study aims to introduce the Hijaiyyah alphabet from the very beginning as a foundation for learning to read the Qur’an, as well as to enhance the use of digital technology in children’s education by employing the Tartiluna Method and Smart TV. The method applied in this study is a qualitative descriptive approach, which collects data through observation, interviews, and documentation. The research subjects included teachers and children at Nasima Kindergarten, Semarang. For data analysis, the data was collected, presented, and summarized. The results of the study indicate that the method of introducing the Hijaiyyah letters using Tartiluna and Smart TV can provide a learning experience that is engaging, effective, and appropriate for the needs of early childhood. The use of Smart TV makes it easier for children to recognize, remember, and pronounce the Hijaiyyah letters correctly. Additionally, the Tartiluna method, which emphasizes calmness and order, when combined with Smart TV technology, created an interactive, fun, and beneficial learning atmosphere for children at an early age.